Clinical valuables related to resolution of complete or advanced atrioventricular block after steroid therapy in patients with cardiac sarcoidosis. Issue 4 (24th June 2021) - Nabeta, Takeru; Hara, Masahiko; Naruke, Takashi; Maemura, Kenji; Oki, Takumi; Yazaki, Mayu; Fujita, Teppei; Ikeda, Yuki; Ishii, Shunsuke; Koitabashi, Toshimi; Ako, Junya
Abstract: Background: Prediction of atrioventricular block (AVB) resolution after steroid therapy in patients with cardiac sarcoidosis (CS) is difficult. Methods: We identified 24 patients with CS and complete or advanced AVB receiving steroid therapy. AVB resolution was assessed by reviewing surface electrocardiogram and the percentage of ventricular pacing required on subsequent device interrogation reports. Results: AVB resolution was noted in eight (33%) patients 1 year after receiving steroid therapy. Univariate Cox regression analysis demonstrated that left ventricular ejection fraction (LVEF) (hazard ratio [HR] 1.07, 95% confidence interval [CI] 1.01‐1.14, P  = .016), interval from recognized AVB to start of steroid therapy (HR 0.98, 95% CI 0.95‐0.99, P  < .001), and lysozyme (HR 1.51, 95% CI 1.12‐2.19, P  = .013) were significantly associated with resolution of AVB. Combination of area under the curve (AUC) of each variable that was significantly related to resolution of AVB (AUC, 0.969; 95% CI 0.921‐1.000, P  < .001) was tended to be higher compared with each variable alone. Conclusions: A shorter interval from recognition of AVB to start of steroid therapy, higher LVEF, and higher lysozyme levels were significantly associated with resolution of AVB after steroid therapy in patients with CS. The combination of each variable could be able to distinguish patients with resolution of AVB from those without. Abstract : Resolution of AVB was observed in 33% patients with CS and AVB after steroid therapy. Univariate analysis demonstrated that a shorter interval from recognition of AVB to start of steroid therapy, higher LVEF, higher lysozyme levels were significantly associated with resolution of AVB after steroid therapy. The combination of each variable associated with resolution of AVB could be able to distinguish patients with resolution of AVB from those without.